Peningkatan Kualitas Hidup Wanita Menopause melalui Pemeriksaan Kesehatan, Senam bersama serta Edukasi Kesehatan Reproduksi di Klinik Universitas Padjadjaran: Improving Knowledge and Quality of Life of Menopausal Women through Reproductive Health Education at the Padjadjaran University Clinic - Bestari, Astuti Dyah; Soebekti, Ghina Salmaa Alfitri; Shofa, Najwa Zahira; Padang, Keisha Avalokita; Rahma, Nadila Nur (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2026)
Menopause is a natural cycle that every woman experiences. The reduction in estrogen during menopause causes both physical and psychological changes. These changes require a challenging adaptation, so proper preparation is essential for women to navigate their menopause optimally. This activity aims to improve the quality of life of menopausal women by increasing knowledge, promoting physical activity, and providing outreach and monitoring of their health and complaints at the Padjadjaran University Clinic. Eleven women aged 43–67 participated in the activity. Blood pressure checks revealed that eight women had pre-hypertension and hypertension. The group exercise session lasted approximately 30 minutes, and all participants performed well. Educational materials included a booklet covering menopause, including its definition, stages, physiological and psychological changes, risk factors for early menopause, nutrition and a healthy lifestyle to reduce menopausal symptoms, support from husbands and families, and when to consult a doctor if experiencing abnormal symptoms. Health workers should not only focus on improving the health of women of reproductive age, but also on the transitional period that occurs in menopausal women, which also requires better attention and management, so that women can experience menopause optimally.